Being beautiful and successful: a bibliometric analysis on the consumption of orofacial harmonization for esthetic purposes, attractiveness, and materialism (Research, Society and Development, 2023)
Actuality there is a consumer trend focused on body image, where being beautiful is synonymous with being successful. The search for attractiveness and the emphasis on materialistic values influence the consumption of products that can enhance appearance. The belief that symmetrical and more attractive faces indicate more successful people can lead to a significant increase in demand for esthetic procedures for orofacial harmonization. A bibliometric study at Web of Science Core Collection (WoS-CC) was conducted on July 03, 2021, to examine the scientific production on the influence of materialism and attractiveness on the demand procedures for orofacial harmonization with esthetic purposes. A search was conducted in WoS-CC from 2005 to 2021. The results showed that the year with the greatest scientific production on the proposed topic was 2020, and the country with the highest number of publications was the United States. The most frequently used keywords were "attractiveness," "beauty," "face," and "body image," and the two most cited authors were Laura Hurd Clarke and Meredith Griffin, who each had 151 citations. The subject area with the highest production was surgery. This study presented an overview of the global trend of scientific production on the subject. The results presented here also allow us to conclude that there seems to be a tendency to study the follow-up of changes in the behavior of the consumer of aesthetic orofacial harmonization procedures.